Legislative norms of space tourism - Mekhovych, E. S.; Pererva, P. G. (My University, 2023)
It has been proven that space tourism is considered a type of tourism that combines the observation of phenomena and objects in outer space during a space flight with the help of space and ground infrastructure for the purpose of using outer space.
Законодавчі норми космічного туризму
Keywords: space tourism; legal regulation; norms; rules; special features